2020
DOI: 10.18821/0869-2084-2020-65-1-42-49
|View full text |Cite
|
Sign up to set email alerts
|

The State and Role of Esophagus, Stomach, Intestinal Microbiota in Patients With Ulcer Disease, Chronic Gastritis, Esophagitis

Abstract: The microflora of 64 biopsies taken during fibrogastroduodenoscopy of the mucous membrane of the esophagus, stomach and duodenum in healthy volunteers and 1120 samples obtained from the same parts of the digestive tract in patients with esophagitis, chronic gastritis and peptic ulcer disease were studied. The patients ranged in age from 18 to 62 years. Traditional bacteriological method was used to isolate and identify microorganisms. Staphylococcus spp., Streptococcus spp., Lactobacillus spp., Bacteroides spp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…increase in inflamed and eroded mucous membranes of the esophagus, stomach, and duodenum. (Chervinets et al, 2020) Pseudomonas aeruginosa is also shown to promote gastric tumorigenesis in colonized rats. (Morishita and Shimizu, 1983) Increases in the abundance of this and other bacteria in patients with bile reflux may reflect a potential relationship between the bile reflux-specific microbiome and the occurrence and development of GC.…”
mentioning
confidence: 99%
“…increase in inflamed and eroded mucous membranes of the esophagus, stomach, and duodenum. (Chervinets et al, 2020) Pseudomonas aeruginosa is also shown to promote gastric tumorigenesis in colonized rats. (Morishita and Shimizu, 1983) Increases in the abundance of this and other bacteria in patients with bile reflux may reflect a potential relationship between the bile reflux-specific microbiome and the occurrence and development of GC.…”
mentioning
confidence: 99%
“…examined 128 phylotypes from human gastric biopsy samples, which were classified into five different bacterial phyla: Proteobacteria , Actinobacteria , Firmicutes , Fusobacteria , and Bacteroidetes ( 12 ). The diversity of microorganisms in the gastric environment was significantly different from that in the oral cavity, esophagus, and intestine ( 9 , 11 13 ). Although the mechanistic events involved in the development of PUD by Helicobacter pylori have been identified ( 6 ), the profile of the microbial community in the stomach at different pathological stages of PUD has not been systematically characterized.…”
Section: Introductionmentioning
confidence: 91%
“…The inflammatory process and severity of PUD may be related to structural changes in the gastric flora ( 10 ). Ecological dysbiosis of the gastric microbiota can induce a significant increase in the number and variety of opportunistic pathogenic bacteria, which can be toxic to cells and induce inflammation in the stomach ( 11 ). Bik et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Помимо H. pylori, микрофлора биоптатов желудка содержит бактерии 6 таксонов, включая: Proteabacteria, Firmicutes, Actinobacteria, Bacteroides, Fusobacteria и Deinococcus. Позитивная роль микробиоты связана с синтезом органических кислот, лизоцима, бактериоцинов и перекиси водорода, конкуренцией за источники питания и рецепторы адгезии, с усилением барьера, подавляющего транслокацию микробов из просвета кишечника во внутреннюю среду макроорганизма, нейтрализацией токсинов и токсических веществ [8]. Стимуляция иммунитета происходит за счет повышения параметров Т-и В-клеточного иммунитета, увеличения авидности антител сыворотки крови к связыванию антигенов патогенных микробов и их токсинов, регуляции синтеза 6-ти провоспалительных и 2-х противовоспалительных (IL-4 и IL-10) цитокинов.…”
Section: Introductionunclassified